INFLUÊNCIA DO INTERVALO ENTRE A PISTA E O ALVO SOBRE AS INIBIÇÕES DO TEMPO DE REAÇÃO MANUAL PROVOCADAS POR PISTAS SIMPLES E MÚLTIPLAS - Silva, Sabrina Guimarães (2009)
When a stimulus occurs unexpectedly in the periphery of the visual hemifield, the stimulus captures automatically the attention for its position. This can produce a facilitation in the detection of the targets that appears in this position with intervals smaller than 100-150ms. Otherwise, if the interval between the first stimulus and the target increases (range 200-1500ms), we can see an opposite effect, because the reaction time increases for responses to targets that appears in that position. In this way, we conducted our experiments with the objective to verify how the Manual Reaction Time (MRT) can be influenced by the stimulation of multiple hemifields in different time intervals. In the tests there were the presentation of 4 different sequences, where the 3 cues can be presented in the same or opposite hemifield of the target. We conducted 6 different experiments where the first five experiments were made by trained subjects in MTRs. In the first the 3 cues and the target presented the same eccentricies and can be presented in the same or opposite hemifields. In the second experiment the cues and the target stimuli presented different eccentricies. In the third and fourth experiments there were two types of trial series: one with the presentation of 3 cues in the same or opposite hemifield of the target and another where only one cue was presented in the same or opposite hemifield of the target. The fifth experiment presents the same paradigm used in the second, except for the cues and the target were presented with the same white color. The last experiment used the same paradigm of the first but it was conducted with non-trained subjects in MRT. The results showed that when a bilateral stimulation of the hemifields occurs, the interval between the cue and the target influences the inhibition of the MRTs. When the interval used was 100ms, there is an inhibition of the MRT in the contralateral condition.